Indonesian Shadow Puppet Recognition Using VGG-16 and Cosine Similarity - Ida Bagus Kresna Sudiatmika; I Gusti Ayu Agung Sari Dewi (STMIK Budi Darma, 2021)
Wayang is one of Indonesia's cultural heritages that must be preserved, where puppets have various functions not only as a means of art, Wayang is also used as a means of religious ceremonies in Indonesia. Therefore, It is very important to preserve the wayang tradition, to preserve it and it is well known by the public, especially young people. In this research, to participate in the preservation of wayang, the authors propose a preservation approach using artificial intelligence and web scraping techniques. Artificial intelligence in this case is carrying out the process of recognizing wayang images and finding information from the puppet data. In searching for information, web scraping techniques are used where information is automatically retrieved from the internet. Information obtained from the internet will be processed using the TF-IDF method and cosine similarity. This study uses the CNN architecture on the existing model, namely VGG-16. The training process is carried out with 200 iterations with an accuracy of 89%. The application of the CNN network architecture and web scraping has been successfully applied and will still be developed in the future to obtain maximum results